Destination Brand Awareness, Association, and Image in Building Agrotourism Destination Brand Equity - Anak Agung Sagung Devi Suamba Pradnyandari; Dwi Putra Darmawan; Gede Mekse Korri Arisena (Jurnal Ecoment Global, 2025)
Abstract   Objective: Destination brand equity is a collection of assets and liabilities of a brand that add or subtract value from a product or service to a company or its customers. Destination brand equity plays a significant role in the characteristics and segmentation of tourist destinations and in increasing tourist loyalty and revenues derived from the destination. Three variables can influence destination brand equity: destination brand awareness, association, and image. This study aims to determine destination brand equity, namely, destination brand awareness, destination brand association, destination brand image, and destination brand equity. Design/Methods/Approach: This study uses a library research method with three main stages: 1) Planning a literature review by determining the research topic through journal searches and academic discussions. 2) Conducting a literature review by collecting and analyzing literature sources related to coffee farmers' income, welfare levels, and food security. 3) Reporting a literature review, namely compiling the results of literature findings systematically based on themes and patterns found in the literature. Findings: This study emphasizes the importance of destination brand awareness, association, and image in building destination brand equity. Originality/Value: This study offers a new perspective on understanding destination brand equity by comprehensively highlighting the role of destination brand awareness, destination brand association, and destination brand image. With a systematic literature study approach, this study contributes to developing a conceptual framework that can be used for further research and provides insight for practitioners in tourism destination management strategies. Practical/Policy implications: Company management recommendations should focus on destination brand awareness, destination brand association, and destination brand image in building the company's destination brand equity. The limitations of this study lie in the limited scope of variables, so further research is needed to obtain other variables with in-depth discussions.   Keywords:Brand; Awareness; Association; Image; Equity